2002
DOI: 10.1086/340487
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic‐Ray Production of6Li by Structure Formation Shocks in the Early Milky Way: A Fossil Record of Dissipative Processes during Galaxy Formation

Abstract: While the abundances of Be and B observed in metal-poor halo stars are well explained as resulting from spallation of CNO-enriched cosmic rays (CRs) accelerated by supernova shocks, accounting for the observed 6 Li in such stars with supernova CRs is more problematic. Here we propose that gravitational shocks induced by infalling and merging subgalactic clumps during hierarchical structure formation of the Galaxy should dissipate enough energy at early epochs so that the CRs accelerated by such shocks can prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(138 citation statements)
references
References 40 publications
3
134
1
Order By: Relevance
“…This is the first theoretical indication of a plateau for these elements which does not resort to exotic models of BBN. This results is in contrast to that found in the structure formation scenario (Suzuki & Inoue 2002), where the medium responsible for cosmic ray acceleration contains very few if any metals, and therefore the CR nucleosynthetic contribution to Be and B in the IGM should be minimal. The latest observations of Be in low-metallicity halo stars, which indicate a hint of a plateau , would then favor a CCR scenario.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This is the first theoretical indication of a plateau for these elements which does not resort to exotic models of BBN. This results is in contrast to that found in the structure formation scenario (Suzuki & Inoue 2002), where the medium responsible for cosmic ray acceleration contains very few if any metals, and therefore the CR nucleosynthetic contribution to Be and B in the IGM should be minimal. The latest observations of Be in low-metallicity halo stars, which indicate a hint of a plateau , would then favor a CCR scenario.…”
Section: Discussioncontrasting
confidence: 94%
“…GCRN builds on the BBN value, yielding a 6 Li abundance which would be proportional to metallicity. Thus, an additional source of 6 Li is required at low metallicity (½Fe/H < À2), and different scenarios have been discussed which include the production of 6 Li during the epoch of structure formation (Suzuki & Inoue 2002;Nakamura et al 2006;Tatischeff & Thibaud 2007) or through the decay of relic particles during the epoch of big bang nucleosynthesis (e.g., Kawasaki et al 2005;Jedamzik et al 2006;Kusakabe et al 2006;Pospelov 2006;Cyburt et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(1), the amount of energetic particles produced by the annihilation process is proportional to the annihilation cross section, and hence the effects on the light element abundances become more enhanced as the cross section becomes larger. Since the light 2 For references, see also [48] for possible astrophysical scenarios to enhance 6 Li abundance, and [49] for its observational uncertainties. 3 The depletion factor D 7 is defined as D 7 = ∆ log 10 ( 7 Li/H).…”
Section: Constraints On Annihilation Cross Sectionmentioning
confidence: 99%
“…Kusakabe et al 2008;Jedamzik & Pospelov 2009 and references therein). Observations of 6 Li/H constrain then the masses/cross-sections/densities of the massive particle; 2) Pre-galactic, by fusion reactions of 4 He nuclei, accelerated by the energy released by massive stars (Reeves 2005) or by shocks induced during structure formation (Suzuki & Inoue 2002;Rollinde et al 2005Rollinde et al , 2006Evoli et al 2008); 3) In situ production by stellar flares, through 3 He+ 4 He reactions (Deliyannis & Malaney 1995) involving large amounts of accelerated 3 He (Tatischeff & Thibaud 2007). Prantzos (2006b) showed that the energetics of 6 Li production by accelerated particles severely constrain any scenario proposed in category (2) above, including jets accelerated by massive black holes; this holds also for the "stellar flare" scenario (3), the parameters of which have to be pushed to their extreme values to obtain the "upper envelope" of the Asplund et al (2006) observations.…”
Section: Earlymentioning
confidence: 99%